2021
DOI: 10.3389/fmicb.2021.636396
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Aminoglycoside Resistance in Human Clinical Klebsiella pneumoniae Complex Isolates and Characteristics of armA-Carrying IncHI5 Plasmids

Abstract: Aminoglycosides are important options for treating life-threatening infections. However, high levels of aminoglycoside resistance (HLAR) among Klebsiella pneumoniae isolates have been observed to be increasing frequently. In this study, a total of 292 isolates of the K. pneumoniae complex from a teaching hospital in China were analyzed. Among these isolates, the percentage of HLAR strains was 13.7% (40/292), and 15 aminoglycoside resistance genes were identified among the HLAR strains, with rmtB being the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, the antimicrobial activity of piperine is higher against Grampositive bacteria as compared to that of Gram-negative bacteria [20]. Despite the high levels of aminoglycoside resistance among Klebsiella pneumoniae isolates observed in previous studies [21], all of K. pneumoniae planktonic cells isolates were susceptible to streptomycin, amikacin, and kanamycin in this study.…”
Section: Discussionmentioning
confidence: 54%
“…However, the antimicrobial activity of piperine is higher against Grampositive bacteria as compared to that of Gram-negative bacteria [20]. Despite the high levels of aminoglycoside resistance among Klebsiella pneumoniae isolates observed in previous studies [21], all of K. pneumoniae planktonic cells isolates were susceptible to streptomycin, amikacin, and kanamycin in this study.…”
Section: Discussionmentioning
confidence: 54%
“…The mechanism of resistance to aminoglycosides mainly occurs due to the presence of aminoglycoside-modifying enzymes (AMEs) and their different ability to modify aminoglycosides. These enzymes include acetyltransferases (AACs), nucleotidyltransferases (ANTs), and phosphotransferases (APHs) were described in Enterobacterales [ 33 ]. In our findings, MICs for gentamicin and/or amikacin showed high-level resistance in 3 isolates expressing various aminoglycosides gene as E4-485, aac(6′)-Ib3 gene; E2-466, aad and aac(3)-IIa genes and K3-441, aac(6′)-Ib and aadA1 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 16S RMTase-encoding genes, especially rmtB and armA , were widely present in Enterobacteriaceae , the coexistence of two or more such genes was unusual. Previous studies found that the two copies of armA combined with six AME genes in one isolate could mediate an extremely high aminoglycosides resistance level (>1,024 mg/L) ( 13 ). These results indicated that the co-occurrence of multiple aminoglycosides resistance genes may result in a higher resistance phenotype.…”
Section: Introductionmentioning
confidence: 99%